Identificação dos líderes de uma comunidade pela técnica reputacional - T Pond, Martin; R Braga, Geraldo (Revista Ceres, 2025)
The objective ofthis study was to identify the leadership of a municipio in Minas Gerais, Brazil and to identify those problems that his leadership considered to be most important.